2023
DOI: 10.3390/ph16020229
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Boswellic Acid Hybrid 1H-1,2,3-Triazoles for Diabetic Management: In Vitro and In Silico Studies

Abstract: A series of 24 new 1H-1,2,3-triazole hybrids of 3-O-acetyl-11-keto-β-boswellic acid (β-AKBA (1)) and 11-keto-β-boswellic acid (β-KBA (2)) was designed and synthesized by employing “click” chemistry in a highly efficient manner. The 1,3-dipolar cycloaddition reaction between β-AKBA-propargyl ester intermediate 3 or β-KBA-propargyl ester intermediate 4 with substituted aromatic azides 5a–5k in the presence of copper iodide (CuI) and Hünig’s base furnished the desired products—1H-1,2,3-triazole hybrids of β-AKBA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…47.5, 45.1, 43.8, 40.9, 39.3, 37.6, 34.2, 34.0, 33.2, 30.9, 29.7, 28.9, 27.5, 27.2, 26.6, 24.7, 21.1, 20.5, 19.9, 18.3, 17.5, 13.8; displayed a molecular ion at m/z 614. 9 HepG2 and RAW 264.7 cell lines were obtained from VACSERA, located in Egypt. The growth of the cells was maintained at 37 °C and 5% CO 2 and in DMEM containing 10% fetal bovine serum and 1% pen−strep antibiotics until reaching 80% confluence.…”
Section: -Eugenyl-2-oxoethyl 2-(3-acetoxy-11-oxo-12ursen-24-oate) (5d)mentioning
confidence: 99%
See 2 more Smart Citations
“…47.5, 45.1, 43.8, 40.9, 39.3, 37.6, 34.2, 34.0, 33.2, 30.9, 29.7, 28.9, 27.5, 27.2, 26.6, 24.7, 21.1, 20.5, 19.9, 18.3, 17.5, 13.8; displayed a molecular ion at m/z 614. 9 HepG2 and RAW 264.7 cell lines were obtained from VACSERA, located in Egypt. The growth of the cells was maintained at 37 °C and 5% CO 2 and in DMEM containing 10% fetal bovine serum and 1% pen−strep antibiotics until reaching 80% confluence.…”
Section: -Eugenyl-2-oxoethyl 2-(3-acetoxy-11-oxo-12ursen-24-oate) (5d)mentioning
confidence: 99%
“…7 The conjugation of a chalcone scaffold with AKBA also leads to improved cytotoxic activity due to its ability to inhibit pin-1 at (IC 50 = 0.97 μM) to AKBA (IC 50 = 50 μM). 8 In another study, click chemistry was used for the formation of boswellic acid triazole hybrids, which give potent α-glucosidase inhibitory activity (IC 50 = 0.43 μM) in comparison to standard acarbose (IC 50 = 942 μM), 9 as shown in Figure 1A. In this context, oleogum resin from frankincense was reported to possess hepatoprotective properties; 10−12 among its constituents, boswellic acids are extensively studied, especially 3-acetyl-11-keto-β-boswellic acid (AKBA), which emerged as a potent anti-inflammatory agents 13−15 Moreover, AKBA is known to bind to receptors in bile and help in restoration of liver normal architecture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has reported several synthesized bioactive 1 H -1,2,3-triazole analogues with potential biological activities including α-glucosidase inhibitors (Figure ). …”
Section: Introductionmentioning
confidence: 99%
“…Their research delved into α-glucosidase inhibition, revealing that all the synthesized derivatives exhibited remarkable potency, exhibiting IC 50 values ranging from 0.22 to 5.32 µM. Notably, these compounds surpassed the efficacy of the standard acarbose by several-fold [12].…”
mentioning
confidence: 99%